2020
DOI: 10.1016/j.psj.2019.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Effect of organic acid mixture on growth performance and Salmonella Typhimurium colonization in broiler chickens

Abstract: Feed additives can be alternatives to antibiotics for routinely encountered pathogens in the poultry production. The objective of this study was to understand effects of organic acid mixture on growth parameters and Salmonella Typhimurium ( ST ) colonization in broilers. Organic acid mixture is a feed-grade buffered formic acid and sodium formate mixture (Amasil NA). A total of 800 1-day-old Cobb500 males were fed one of the five dietary treatments: a negative cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
1
16
1
Order By: Relevance
“…All data were analyzed in the PROC GLM program of SAS software (SAS Institute Inc., Cary, NC, USA). For bird mortality, the number of dead birds per pen was transformed by the formula below [ 19 ]. …”
Section: Methodsmentioning
confidence: 99%
“…All data were analyzed in the PROC GLM program of SAS software (SAS Institute Inc., Cary, NC, USA). For bird mortality, the number of dead birds per pen was transformed by the formula below [ 19 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Gonzalez-Fandos et al (2020) reported that citric acid solution reduced the growth of Listeria monocytogenes on poultry legs stored at 4 °C for 8 days. Adhikari et al (2020) found that addition of 0.9% organic acid (mainly sodium format) in the diet of broilers resulted in reversing the Salmonella typhimurium colonization in broiler chickens. Mortada et al (2020) concluded that organic acid (formic acid, cinnamaldehyde) significantly inhibited the proliferation of Campylobacter coli population in the in vitro study although its effect on cecal load and carcass surface remained no significant.…”
Section: Antimicrobial Effect Of Organic Acidmentioning
confidence: 99%
“…Various preharvest and postharvest antimicrobial interventions are being used during poultry production and processing to reduce Salmonella prevalence, thus controlling Salmonella associated foodborne illnesses. Some of the most commonly used feed additives during poultry production are organic acids, probiotics, prebiotics, herbal extracts, and nutraceutical products ( Abudabos et al, 2018 ; Teng and Kim, 2018 ; Yadav and Jha, 2019 ; Adhikari et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%